Ceramic processing of magnesium diboride - Dancer, C (2008)
This thesis describes the fabrication and characterization of ex situ magnesium diboride (MgB2) bulk material to study its sintering behaviour. Since the discovery of superconductivity in magnesium diboride in 2001, many research studies have identified the attractive properties of this easy-to-fabricate, low cost superconductor which can attain high critical current density even without heat-treatment. However there is little consensus in the literature on the processing requirements to produce high quality MgB2 material with low impurity content and high density. In this work, the key parameters in the production of dense ex situ MgB2 produced from Alfa Aesar MgB2 powder are established by examining the effect of modifying the characteristics of the starting material and the processing parameters during pressureless and pressure assisted heat-treatment. The particle size distribution, impurity content and particle morphology of Alfa Aesar MgB2 powder were determined using laser dffraction, X-ray diffraction, X-ray photoelectron spectroscopy, electron dispersive spectroscopy, scanning electron microscopy and transmission electron microscopy. This powder was also modified by separation (sieving and sedimentation) and milling (ball milling and attrition milling), with changes made to the powder determined by the same techniques. A pressureless heat-treatment method using a magnesium diboride powder bed was developed. This minimised MgO formation in samples produced from as-purchased MgB2 powder to less than 8 wt.% for heat-treatment at 1100°C. MgO content was determined by X-ray diffraction using calibrated standards. MgB2 bulk material was produced from as-purchased and modified powders by pressureless heat-treatment under Ar gas, and characterized using Archimedes' density method, X-ray diffraction, Vickers hardness testing, scanning electron microscopy, and magnetization measurements. Very limited densification was observed for all samples prepared by pressureless heat-treatment, with only limited increases in connectivity observed for some samples heat-treated at 1100°C. Pressure-assisted bulk samples were prepared from as-purchased MgB2 and selected modified powders using resistive sintering, spark plasma sintering, and hot pressing. These were characterized using the same techniques, which indicated much more extensive densification with similar levels of impurity formation as for pressureless heat-treatment at 1100°C. The results indicate that densification and applied pressure are strongly correlated, while the effect of temperature is less significant. The optimum processing environment (inert gas or vacuum) was dependent on the technique used. These results indicate that pressure-assisted heat-treatment is required in order to produce dense bulk MgB2.